2021
DOI: 10.1177/1934578x20984609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dehydrothermal Treatment on the Mechanical Properties and Biocompatibility of Plaster of Paris–CaCO3Hydrogel Loaded With Cinnamaldehyde for Biomedical Purposes

Abstract: CaCO3 hydrogel incorporation into Plaster of Paris (POP) formulations decreased the resorption rate of the POP after implantation in the body. Although an inflammatory process is required as part of wound healing, the accumulation and activation of inflammatory cells in the POP–hydrogel CaCO3 implant area needs to be controlled. Therefore, cinnamaldehyde, as an anti-inflammatory agent with a unique α, β-unsaturated aldehyde, was incorporated into the CaCO3 hydrogel. During the incorporation, both the lipophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…April 2023; 9(1): 22-29 ISSN 2460-0164 (print) ISSN 2442-2576 (online) 24 HE, Mallory, Toluidine Blue, TRAP, dan DAB. 6,10 At least three parts of the tissue around the implant (soft and hard tissue) were examined with a light microscope (Nikon eclipse E600) with an Optilabviewer® to draw images at magnification from 10X10 to 100X10. Description analysis was performed on the response of soft tissues and hard tissues to implants.…”
Section: Methodsmentioning
confidence: 99%
“…April 2023; 9(1): 22-29 ISSN 2460-0164 (print) ISSN 2442-2576 (online) 24 HE, Mallory, Toluidine Blue, TRAP, dan DAB. 6,10 At least three parts of the tissue around the implant (soft and hard tissue) were examined with a light microscope (Nikon eclipse E600) with an Optilabviewer® to draw images at magnification from 10X10 to 100X10. Description analysis was performed on the response of soft tissues and hard tissues to implants.…”
Section: Methodsmentioning
confidence: 99%
“…Gelatin is a kind of protein and also has many functional groups, including amino groups. Dewi et al prepared a Plaster of Paris–CaCO 3 hydrogel containing gelatin, in which gelatin was conjugated with cinnamaldehyde via imine linkages, and the results regarding physical properties in vivo biocompatibility showed that it may be a promising bone substitute containing cinnamaldehyde as an anti-inflammatory agent [ 79 ].…”
Section: The Applications In the Biomedical Fieldmentioning
confidence: 99%
“…We employed dehydrothermal (DHT) treatment to generate the formation of intermolecular crosslinks through a condensation reaction in a functional group of gelatin to decrease the crosslink effect capability of cinnamaldehyde. 12 Crosslinking gelatin can be achieved by physical treatments, such as heat (DHT), UV radiation, and gamma radiation, and chemical treatments, for example aldehydes (such as formaldehyde, glutaraldehyde (GA) or glyceraldehyde), polyepoxides, and isocyanates. 13 GA is currently the most used crosslinking molecule because it is inexpensive, and it works well with collagen-based materials.…”
mentioning
confidence: 99%